Genetic relatedness and sex predict helper provisioning effort in the cooperatively breeding noisy miner. (18th August 2018) - Barati, Ahmad; Andrew, Rose L; Gorrell, Jamieson C; Etezadifar, Farzaneh; McDonald, Paul G
Abstract : The benefits that helpers gain from aiding other individuals is thought to be shaped largely by their relatedness to the individuals they help. We investigated this in cooperatively breeding noisy miners and found that the majority of help was provided by relatives, primarily male birds. Sex-biased helping is likely a result of females dispersing to new areas whereas males do not, and therefore have a greater degree of contact with relatives. Abstract: Cooperative breeding is a breeding system in which offspring receive care not only from their parents but also from other conspecific helpers. This helping behavior could potentially be costly to attendants; however, one of the means by which helpers can override these costs is through preferentially directing aid towards kin. Helping patterns might vary according to helper sex if sex-biased dispersal is present. Here, we examined how genetic relatedness and sex of helpers shaped their provisioning behavior in the noisy miner ( Manorina melanocephala ). This common Australian passerine lives year-round in large colonies that contain both related and unrelated individuals. There was a strong sex-bias in helper effort, with 93% of helpers being philopatric males that remain in natal colonies for life, even though males make up only 69% of the population. Females dispersed prior to breeding and rarely helped at the nest. Helpers varied in their level of relatedness to the breeders which positively predicted their provisioning rate and biomass delivered to the broods, with the majority of help provided by related helpers. These results show that there was a clear sex difference in helping behavior in this species; with related males, most likely retained offspring from previous years, being the main providers of aid among all helpers. Kinship and patterns of philopatry, therefore, appear to be important drivers of helping behavior in noisy miners, although given that unrelated helpers also provisioned young at substantial levels, other types of direct benefits may further play a role in maintaining cooperatively breeding in this species.